Single‐Atom Iron Anchored Tubular g‐C3N4 Catalysts for Ultrafast Fenton‐Like Reaction: Roles of High‐Valency Iron‐Oxo Species and Organic Radicals - Chen, Fei; Liu, Lian‐Lian; Wu, Jing‐Hang; Rui, Xian‐Hong; Chen, Jie‐Jie; Yu, Yan (Advanced materials (Weinheim), 2022)
Single‐atom catalysts have emerged as an efficient oxidant activator for eliminating organic pollutants in Fenton‐like systems. However, the complex preparation, single active site, lack of understanding of the fundamental mechanism, and harsh pH conditions currently limit their practical applications. In this work, single‐atom iron anchored nitrogen‐rich g‐C3N4 nanotubes (FeCNs) are designed and synthesized by a facile approach, and eco‐friendly peracetic acid (PAA) is selected as the oxidant for Fenton‐like reactions. The constructed heterogenous system achieves an enhanced degradation of various organic contaminants over a wide pH range of 3.0–9.0, exhibiting an ultrahigh and stable catalytic activity, outperforming equivalent quantities of pristine g‐C3N4 by 75 times. The 18O isotope‐labeling technique, probe method, and theoretical calculations demonstrate that the efficient catalytic activity relies on the high‐valency iron‐oxo species coupled with organic radicals generated by PAA. An increase in electron transport from the contaminant to the formed “metastable PAA/FeCN catalyst surface complex” is detected. A double driving mechanism for the tubular g‐C3N4 regulated by a single Fe site and PAA activation is proposed. This work opens an avenue for developing novel catalysts with the coexistence of multiple active units and providing opportunities for significantly improving catalytic efficiency. Atomically dispersing Fe(III) sites into fine‐tuned nitrogen‐rich graphitic carbon nitride nanotubes are designed for peracetic acid activation and further for Fenton‐like reactions. This work opens a new avenue to develop heterogenous catalytic systems with higher reactivity and better durability using a double engine mechanism.